2018
DOI: 10.1186/s12963-018-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy inequalities in the elderly by socioeconomic status: evidence from Italy

Abstract: BackgroundLife expectancy considerably increased in most developed countries during the twentieth century. However, the increase in longevity is neither uniform nor random across individuals belonging to various socioeconomic groups. From an economic policy perspective, the difference in mortality by socioeconomic conditions challenges the fairness of the social security systems. We focus on the case of Italy and aim at measuring differences in longevity at older ages by individuals belonging to different soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
0
31
1
2
Order By: Relevance
“…This finding might be due to greater differences in occupational burden between SES groups among men than among women. 14 35 36 Overall, the increase in life expectancy for women is much weaker than for men, leading to a narrowing gender gap, which can also be observed for the total German population. 1 Due to the considerably small increase in female life expectancy, changes in inequalities over time were expected to be less pronounced for women than for men, which holds true for our study population.…”
Section: Discussionmentioning
confidence: 83%
“…This finding might be due to greater differences in occupational burden between SES groups among men than among women. 14 35 36 Overall, the increase in life expectancy for women is much weaker than for men, leading to a narrowing gender gap, which can also be observed for the total German population. 1 Due to the considerably small increase in female life expectancy, changes in inequalities over time were expected to be less pronounced for women than for men, which holds true for our study population.…”
Section: Discussionmentioning
confidence: 83%
“…in Southern Italy the life expectancy is 79.9 years for males and 84.4 years for females, while in Northern Italy it is 81.1 years for males and 85.6 for females). Interestingly, a recent study showed that when controlling for the typology of pension benefit and socioeconomic conditions, people from Northern Italy are characterized by a higher mortality risk compared to populations from Central Italy, while no significant differences between Central and Southern Italians emerged [ 44 ]. We can thus speculate that Central and Southern Italians may have got a head start in the race for longevity, but that present-day local socio-economic status hides or alters the impact of longevity-associated genetic components.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing retrospective data on the gender distribution of domestic and care work in the Survey of Health, Ageing, Retirement in Europe (SHARE), Addabbo et al (2014) found a poorer global health status and residual affective problems for women with children and who defined themselves as having the main responsibilities in care work. Life expectancy significantly differs according to socioeconomic status, with a higher life expectancy for the self-employed and a difference of more than five years between individuals with different socioeconomic statuses, thus confirming large health inequalities, a finding that brings into question the fairness of the Italian public pension system (Lallo and Raitano 2018).…”
Section: Healthmentioning
confidence: 85%